2010
DOI: 10.1136/adc.2010.186056
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between bacterial and aseptic meningitis in children: European comparison of two clinical decision rules

Abstract: The Meningitest and the BMS were both 100% sensitive. This result provides level II evidence for the sensitivity of both rules, which can be used cautiously. However, use of the BMS could safely avoid significantly more unnecessary antibiotic treatments for children with AM than can the Meningitest in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 18 publications
5
50
0
2
Order By: Relevance
“…17,18 Evidence from adult meningitis patients suggests that CSF lactate level and serum procalcitonin level would be better discriminative parameters for bacterial meningitis, however, the cost of both examinations limits their availability. 5,19,20 The current study concentrated on basic CSF and blood examinations that can be carried out in ordinary laboratories, even in laboratories in remote rural areas. The results showed that a low CSF WBC count with increased protein levels and/or decreased glucose levels correlated with poor outcomes of the pediatric patients with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Evidence from adult meningitis patients suggests that CSF lactate level and serum procalcitonin level would be better discriminative parameters for bacterial meningitis, however, the cost of both examinations limits their availability. 5,19,20 The current study concentrated on basic CSF and blood examinations that can be carried out in ordinary laboratories, even in laboratories in remote rural areas. The results showed that a low CSF WBC count with increased protein levels and/or decreased glucose levels correlated with poor outcomes of the pediatric patients with bacterial meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of this prediction model was confirmed in a retrospective validation study (n = 500) [8], but these authors proposed a new diagnostic model (AUC close to 1) based on four different independent variables (CSF protein, CSF PMN, blood glucose and blood WBC). These findings evoked the interest of other groups to validate the various diagnostic prediction models, and also to introduce new self-computed models that showed varying degrees of sensitivity (77%-98%) and specificity (49%-98%) for predicting bacterial meningitis in neonates, children and adults [9][10][11][12][13][14].…”
Section: Cerebrospinal Fluid (Csf)mentioning
confidence: 99%
“…Bakteriyel ve aseptik menenjit ayrımında serum prokalsitonin düzeyinin ≥ 0,5 ng/mL, > 2 ng/mL, > 4,8 ng/mL, ≥ 5 pg/mL düzeylerindeki kesim noktalarındaki duyarlılığı %100-89 ve özgüllüğü %93,5-66 arasında değiştiği rapor edilmiştir (13)(14)(15)(16)(17). Bu çalışmaların bir kısmında prokalsitoninin, CRP ve tam kan sayımı parametrelerine göre bakteriyel menenjiti öngörmede daha duyarlı bir laboratuvar testi olduğu bildirilmiştir (14)(15)(16)(17).…”
Section: Discussionunclassified